The increased effectiveness of resistance training on unstable vs. stable surfaces on selected measures of physical performance in young male soccer players - Sanchez-Sanchez, J.; Raya-González, J.; Ramirez-Campillo, R.; Chaabene, H.; Petisco, C.; Nakamura, F. Y. (The Journal of Strength and Conditioning Research, 2022)
To examine the effects of 10-week (2/wk) resistance training on stable vs. unstable surfaces on selected measures of physical performance in young male soccer players, national-level U19 players participated in this study. They were randomly allocated to an unstable resistance training group (uRT, n = 27) or a stable resistance training group (sRT, n = 28). Before and after the training, horizontal jumping with dominant (Hop D) and nondominant leg (Hop non-D), repeated sprint ability (RSA best time [RSAbest] and RSA mean time [RSAmean]), change-of-direction (COD) speed (Illinois COD test), and aerobic endurance (YoYo Intermittent Recovery Test Level 1 [YoYo IR1]) were assessed. To establish the effects of the interventions on the dependent variables, a 2 (group: uRT and sRT) × 2 (time: pre, post) analysis of variance with repeated measures on time was computed. A significant main effect of time was observed for Hop non-D, RSAbest, and RSAmean (p = 0.003-0.06, effect size [ES] = 0.06-0.15). Furthermore, significant group × time interactions were shown for RSAbest (p = 0.007, ES = 0.13) and RSAmean (p = 0.002, ES = 0.2). Post hoc analysis revealed significant pre- to post-training improvements for RSAbest (p = 0.002, ES = 0.35) and RSAmean (p = 0.0002, ES = 0.36) in the uRT. In the sRT, however, no significant pre-post performance changes were observed in RSAbest and RSAmean. In conclusion, 10 weeks of an in-season resistance training on unstable conditions in addition to regular soccer training was effective in improving repeated-sprint ability performance in youth male elite soccer players including maximal linear sprinting and the ability to perform repeated sprint.